EFL Students in Speaking Skill: Identifying English Education Students’ Perceptions of the Psychological Problems in Speaking - Ikrar Genidal Riadil (JETAL: Journal of English Teaching & Applied Linguistic, 2020)
This research focuses on students' English speaking problems, and this research aims to find out the most dominant problem of speaking in English as a Foreign Language (EFL) situation faced by the students of English Departement at Tidar University. The research method used in this research is the qualitative method. The writer uses a questionnaire as a tool for data collection. From the questionnaire, the problems that most dominant faced by the English education students of the English Department at Tidar University is Linguistic problems. Linguistic problems include less grammar, lack of vocabulary, and poor pronunciation. The next is psychological problems include, including lack of self-confidence, anxiety, and shyness. Meanwhile, instructor related problems did not have much effect on speaking problems for the students. In conclusion, Linguistic problems are the most dominant problem faced by the English education students of the English Department at Tidar University.